2018
DOI: 10.1186/s13089-018-0099-y
|View full text |Cite
|
Sign up to set email alerts
|

ABCDE of prehospital ultrasonography: a narrative review

Abstract: Prehospital point-of-care ultrasound used by nonradiologists in emergency medicine is gaining ground. It is feasible on-scene and during aeromedical transport and allows health-care professionals to detect or rule out potential harmful conditions. Consequently, it impacts decision-making in prioritizing care, selecting the best treatment, and the most suitable transport mode and destination. This increasing relevance of prehospital ultrasonography is due to advancements in ultrasound devices and related techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 151 publications
1
23
0
3
Order By: Relevance
“…There are some other published papers, which reported that EMS physicians and paramedics without prior ultrasonography training can be trained effectively after a short course (16)(17)(18)(19). Overall, it seems that ultrasound in Iran, like many developed countries, is going to be widely used in the prehospital emergency system (20). But the structure of this organization in our country is very different from that of the rest of the world, and naturally, different planning needs to be designed in order to make the best use of this tool in the pre-hospital setting.…”
Section: Discussionmentioning
confidence: 96%
“…There are some other published papers, which reported that EMS physicians and paramedics without prior ultrasonography training can be trained effectively after a short course (16)(17)(18)(19). Overall, it seems that ultrasound in Iran, like many developed countries, is going to be widely used in the prehospital emergency system (20). But the structure of this organization in our country is very different from that of the rest of the world, and naturally, different planning needs to be designed in order to make the best use of this tool in the pre-hospital setting.…”
Section: Discussionmentioning
confidence: 96%
“…[41][42][43][44][45] Many other applications have been described which can be of use in certain care environments or on a case-bycase basis. 10 Table 1 provides an overview of common PHUS exam types, indications, and clinical use examples.…”
Section: Clinical Applications and Outcomesmentioning
confidence: 99%
“…POCUS performed in the pre-hospital and mass casualty incidents may affect the clinical decisions, noti cations, transport modes, and hospital destination [3]. Pre-hospital POCUS was established two decades ago in various pre-hospital emergency medical services (EMS) in Europe, Australia, and North America [6,7]. It was available in 9% of the French EMS units [8] and in 4.1% in the USA and Canada [9].…”
Section: Introductionmentioning
confidence: 99%